2019
DOI: 10.3390/molecules24101880
|View full text |Cite
|
Sign up to set email alerts
|

High Production of Chitinolytic Activity in Halophilic Conditions by a New Marine Strain of Clonostachys rosea

Abstract: Twenty-eight fungal strains have been isolated from different natural marine substrates and plate screened for their production of chitinolytic activity. The two apparent best producers, Trichoderma lixii IG127 and Clonostachys rosea IG119, were screened in shaken cultures in media containing 1% colloidal chitin, 1% yeast nitrogen base and 38‰ NaCl, for their ability to produce chitinolytic enzymes under halophilic conditions. In addition, they were tested for optimal growth conditions with respect to pH, sali… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
18
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
3
2

Relationship

2
6

Authors

Journals

citations
Cited by 28 publications
(20 citation statements)
references
References 46 publications
2
18
0
Order By: Relevance
“…For instance, C. sphaerospermum [61], C. ramotenellum [62], P. brevicompactum [63], E. nigrum [62], C. rosea [64], and R. oryzae [65] are mainly known from terrestrial environments, but they are also found in deep sea (C. sphaerospermum) [66], Dead Sea water (C. ramotenellum, P. brevicompactum) [67], river sediments (C. rosea) [68], associated with marine sponges (E. nigrum, P. brevicompactum) [69,70], bryozoan Bugula sp. (R. oryzae) [71] or with seagrasses Posidonia oceanica (C. rosea) [72]. To the best of our knowledge, this is the first study that isolated T. paraviridescens from a marine environment.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…For instance, C. sphaerospermum [61], C. ramotenellum [62], P. brevicompactum [63], E. nigrum [62], C. rosea [64], and R. oryzae [65] are mainly known from terrestrial environments, but they are also found in deep sea (C. sphaerospermum) [66], Dead Sea water (C. ramotenellum, P. brevicompactum) [67], river sediments (C. rosea) [68], associated with marine sponges (E. nigrum, P. brevicompactum) [69,70], bryozoan Bugula sp. (R. oryzae) [71] or with seagrasses Posidonia oceanica (C. rosea) [72]. To the best of our knowledge, this is the first study that isolated T. paraviridescens from a marine environment.…”
Section: Discussionmentioning
confidence: 90%
“…To the best of our knowledge, this is the first study that isolated T. paraviridescens from a marine environment. However, other species of Trichoderma have previously been found in marine sediments, marine sponges, mangroves, brown algae [72][73][74].…”
Section: Discussionmentioning
confidence: 99%
“…In the last decades, the interest in marine and marine derived fungi has been growing due to their high e cacy in the synthesis of secondary metabolites [4,5,[10][11][12][13][14][15][16][17][18]. These organisms are also promising sources of enzymes useful in different technological applications [19][20][21]. In this context, halophilic fungi have been applied in the ne and specialty chemical elds, as well as in the production of biodiesel and bioremediation [9,[22][23][24][25][26].…”
Section: Introductionmentioning
confidence: 99%
“…In particular, fungi related to leaf district are characterized by a high content of tannic acids and represent an interesting source of new bioactive molecules [29]. A great heterogeneity of fungal colonisers from different posidonia meadows in Tyrrhenian Sea was reported [30][31][32], and their biotechnological application is still increasing [20,29]. Mariannaea humicola, belonging to Ascomycetes (Hypocreales, Nectriaceae), is generally recognised as a soil saprophytic fungus (ethimology: name refers to the soil substrate from which this fungus was isolated), [33].…”
Section: Introductionmentioning
confidence: 99%
“…In the last decades, the interest in marine and marine derived fungi has been growing due to their high e cacy in the synthesis of secondary metabolites [4,5,[10][11][12][13][14][15][16][17][18]. These organisms are also promising sources of enzymes useful in different technological applications [19][20][21]. In this context, fungi isolated in highly stressing environments (i.e.…”
Section: Introductionmentioning
confidence: 99%